Effect of financial innovation and stakeholders' satisfaction on investment decisions: Does internet security matter? - Jean Baptiste Bernard Pea-Assounga; Hongxing Yao; Grace Mulindwa Bahizire; Prince Dorian Rivel Bambi; Jonathan Dior Nima Ngapey (Heliyon, 2024)
This research suggests a study model of determinants of investment decisions in the context of financial innovation. The paper considers the technology innovation dimension, which influences stakeholders' (customer and employee) satisfaction, bank performance, and investment decisions. This research aims to bridge the gap by analyzing the effect of the innovation component, financial innovation on investment decisions and considering the mediated link via stakeholders' satisfaction and the bank's performance as well as the moderating role of Internet security (IS) and utilizing data gathered from 575 banks' employees and customers in Congo. Employing Structural Equation Modelling to evaluate the hypotheses, the research obtains that: (1) financial innovation (FI) is negatively associated with investment decisions (ID), and positively related to employee satisfaction (ES), customer satisfaction (CS), and bank performance (BP). (2) BP, CS, ES, and IS are related significantly and positively to ID. (3) BP, CS, and employee satisfaction do mediate the relationship between FI and ID. (4) Internet security does not moderate the effect of FI on ID. The investigation emphasizes the role of financial innovation and Internet security in investment decision-making for the providers of financial innovation services. Certainly, it recommends that financial institutions should consider this as well as internet security in their investment decisions. This article contributes to financial literature and bank management by offering supporting theories and a framework that facilitates the identification of pertinent strategic resources and constructs.